Direct microwave leaching conditions of rare earth elements in fluorescent wastes - Bilen, A.; Birol, B.; Saridede, M. N.; Kaplan, S. S.; Sonmez, M. S. (ELSEVIER, 2024)
The luminescent phosphor powder in the fluorescent lamp constitutes 2% of the lamp's weight. It can be mentioned that fluorescent wastes are a crucial raw material to produce rare earth oxides. In the present study, microwave leaching process was conducted to dissolve rare earth elements yttrium (Y), europium (Eu), and remaining rare earth elements (REEs) present in the phosphor powder of the fluorescent lamp, and the yields were compared. In the microwave leaching process, the effects of the temperature (80 -160 degrees C), acid type (hydrochloric acid (HCl), nitric acid (HNO3), sulphuric acid (H2SO4)), acid concentration (0.5-6 mol/L), solid to liquid ratio (0.1:10-0.5:10) and reaction time (5-90 min) parameters on leaching efficiencies of varying rare earth elements and calcium were investigated. The highest yield was obtained in the direct microwave leaching of fluorescent waste with the experimental conditions of 6 mol/L HCl, 160 degrees C, 0.1:10 solid-to-liquid ratio (S:L), and 90 min. Activation energy calculations were made, and kinetic models of the reactions were obtained, and it is observed that Y and Eu dissolution is diffusion-controlled, on the other hand, lanthanum (La), cerium (Ce), and terbium (Tb) were examined to be chemical reaction controlled. Moreover, calcium (Ca) and gadolinium (Gd) seem coherent with the mixed model. Concurrently, mathematical models of all experimental studies are created with the response surface Box-Behnken method and the correlation coefficients of all the models are over 90%. (c) 2023 Chinese Society of Rare Earths. Published by Elsevier B.V. All rights reserved.
Keywords: Rare earth elements (REEs); Direct microwave leaching; Fluorescent waste; Kinetic models; Response surface method; HYDROMETALLURGICAL PROCESS; LAMP WASTE; RECOVERY; METALS; CONCENTRATE; DECOMPOSITION; PHOSPHORS; EXTRACTION; YTTRIUM; POWDERS; Chemistry